DIFFERENCES BETWEEN AUSTRALIAN INDIGENOUS AND NON-INDIGENOUS MAINTENANCE HEMODIALYSIS PATIENTS - Alwyn Todd; Anthony Meade; Robert Carroll; O'Dea; Stephen MacDonald (The Korean Society of Nephrology, 2012)
Indigenous Australians have an increased incidence of kidney disease and decreased survival on hemodialysis. The aim of this study was to investigate whether differences in nutritional status exist between indigenous and non-indigenous patients undergoing maintenance hemodialysis in South Australia. Seventy-two (22 Australian indigenous, 50 non-indigenous) stable hemodialysis patients were enrolled in a three month cross-sectional study. During the study patients underwent routine hemodialysis treatment and biochemical tests. Weight and biochemical measurements were collected pre and post dialysis on the first Tuesday or Wednesday of each month. A patient generated subjective global assessment (PG-SGA) was conducted in the third month of the study. Pre-dialysis albumin was 32.8+/4.1g/L in Australian indigenous patients and 36.2+/-4.5g/L in non-indigenous patients (p= 0.003). The difference between pre-dialysis and post-dialysis albumin was -4.0+/-2.8g/L in indigenous patients and -1.0+/-1.9g/L in non-indigenous patients (p=0.000). Intra-dialytic weight gain was 3.0+/-2.6kg in indigenous patients and 2.0+/-0.8kg in non-indigenous patients (p=0.010). Serum sodium and bicarbonate were 136.2+/-2.7mmol/L and 22.3+/-1.7mmol/L in indigenous patients and 138.5+/-2.3mmol/L and 25.2+/-5.8mmol/L in non-indigenous patients (p=0.010,0.003). Glucose, HbA1c and triglyceride were 9.7+/-4.6mmol/L, 7.0+/-1.7% and 2.2+/-1.3mmol/L in indigenous patients and 7.0+/-2.8mmol/L, 6.2+/-1.0% and 1.4+/-0.7mmol/L in non-indigenous patients (p= 0.005, 0.047, 0.016). No differences were observed in dry weight, PG-SGA, post-dialysis albumin, serum potassium, urea, creatinine, parathyroid hormone, phosphate, calcium, C-reactive protein or hemoglobin. This study indicates that differences exist between Australian indigenous and non-indigenous maintenance hemodialysis patients, with indigenous patients less likely to be meeting recommendations.